THE RISE OF REMOTE WORK, EVALUATING THE PROS AND CONS OF WORKING FROM HOME - Ulugbek Yarashovich Elmurodov (European Science Publishing, 2024)
The article addresses the rise of online work following a global health crisis. It is particularly useful for individuals undecided about the most suitable type of work for them, as it systematically compares the advantages and disadvantages of working from home. The key aspects of this work model are analyzed, highlighting its global preference levels. Additionally, the article outlines the conditions conducive to e-working and emphasizes the strategic benefits of home-based work. This comprehensive analysis aims to provide a clear understanding of whether remote work is a suitable option based on individual circumstances and career goals.
Keywords: online-home based work, freelance, global health crisis, job creation, unemployment, pros and cons of e-working, internet connection, benefits, skills, opportunities